ELEMENTATA ARTISTIK PADA PROGRAM ACARA LANGEN SWARA JOGJATV - Suprobo, Bondhan Hafsari; Kurniawan, Donie Fadjar (Capture : Jurnal Seni Media Rekam, 2013)
This research is to know what Langen Swara program broadcasting in Jogja TV as atalkshow program which has locality culture contents based on its artistics. The purpose of thisresearch describes the artistic elements which are combined with locality culture.The form ofthis research is descriptive qualitative and basic research.Then,for the first time data is collecteduntil ready to summarized. Furthermore,interview is the best way to collect the main data.Theresults is that Langen Swara program used television artistic setting, make-up and wardrobe,acting, and lighting.All of the artistic elements and locality were from Banyumas as a simbol ofBanyumas culture.Keywords: Artistics,local identity,and Langen Swara